FAKTOR-FAKTOR YANG MEMPENGARUHI SISWA MELANGGAR TATA TERTIB SEKOLAH DI MTs AL FALAH JATIBARU KECAMATAN BUNGARAYA KABUPATEN SIAK - Ikbal Maulana; Zahirman Zahirman; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak:This research is motivated by factors that affect students in violating the rules of school in MTs Al Falah Jatibaru Bungaraya District Siak Regency. The formulation of the problem in this researchis